Waste cooking oil-based polyurethane solid polymer electrolyte : The effect of isocyanate structure / Nor Azmiera Kamarulzaman - Kamarulzaman, Nor Azmiera (Faculty of Applied Sciences, 2017)
Waste cooking oil-based polyurethane was prepared via solvent-free method using waste cooking oil based polyol (WCO-p) and 4,4- diphenylmethane diisocyanate (MDI) or 1,6- hexamethylene diisocyanate (HDI) with lithium trifluoromethane sulfomide (LiTFSI) salt and ethylene carbonate (EC) as plasticizer. The polyurethane films were examined using Fourier Transform Infrared Spectroscopy (FTIR) and Electrochemical Impedance (EIS), Differential Scanning Calorimetry (DSC) and X-Ray Diffraction (XRD). The ionic conductivity from EIS result of the polyurethane film mixed with MDI and salt are higher which is 5.76 x10-6 Scm-1compared to film mixed with HDI and salt 6.03 x10-7 Scm-I. This was proved by XRD analysis which is more amorphous than PU-HDls. However the glass transition is highest temperature due to sterlc hindrance of benzene ring in hard segment for PU-MDls. FTIR analysis showed the absence of the band in the range of 2260 to 2310 cm-I proves there is no free NCO group that confirms the urethane reaction is complete in the structure of polymer. However that band is presence at 2276.05 cm-I in PU-MDI spectrum showed not all of the isocyanate groups reacted during polymerization.